The Parametric Estimation of Tidal Potential Power Density using Modeling Strategies at Hajambro Creek of Indus Delta, Pakistan: Development of Tidal Potential Power Density Models for Hajambro Creek, Pakistan - Baig, Mirza Salman; Uddin, Zaheer; Insaf, Ambreen (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
There are many accessible resources for electricity generation using renewable energy, like, solar, wind, tidal and wave etc. The output of all these resources depend on weather conditions, force of gravity or rotation of the Earth, but tidal energy has a major advantage over many other forms of renewable generation as it is predictable over a long period of time. Pakistan has about 1000 km long coastline with complex network of creeks in the Indus delta region which include 17 major creeks and further divide into a number of estuaries with considerable tidal ranges and tidal current. This research study is carried out at one of these major creeks namely Hajambro (Hajambro river) and extends from Hajambro 24ᵒ 08’N 67ᵒ 22’E (sea mouth) to Keti Bander 24ᵒ 09’N 67ᵒ 27’E (mouth of river Indus). Study area is targeted within creek region where there is a large shortfall of electricity observed and this situation has threaten the community socioeconomically. In this research study, available tidal energy resources of Hajambro creek are assessed, tidal power density models and bathymetry model are developed in Arc-GIS (geographical information system) environment, for the first time. A comprehensive tidal turbine technology review is conducted and based on up-to-date tidal turbine technology review and results achieved from assessment of tidal energy resources, deployment of a turbine at Hajambro creek is proposed. With effective area of 9.46 km2 mean spring estimated power (seasonally) is observed as 14 MW in winter, 12.9 MW in Pre-Monsoon, 13.6 MW in Monsoon and 13.1 MW in Post-Monsoon.